Autograft cranioplasty for skull defects in children - Mohammad Fekry Elshirbiny; Assem Ahmed; Mohamed Mohsen Amen (Interdisciplinary Neurosurgery, 2023)
Background: Cranioplasty is a commonly performed neurosurgical procedure. Cranioplasty is a surgical repair of bony defects in the skull resulting from previous surgery or injury. The pediatric population differs from the adult population as the skull keeps growing and needs special consideration. Aim of the work: This study was conducted to report the experience of the University of Mansoura in children undergoing various bone autografts for cranioplasty over a period of four years. Patients and methods: This retrospective study of hospital records of children undergoing cranioplasty at the Department of Pediatric Neurosurgery, Mansoura University Hospital between 2018 and 2022. Sex, age, cause of cranial defect, time since craniectomy, type of graft used, bone fixation, cosmetic outcome, wound healing, complications, and treatment of complications were reported. Results: Data from forty-two children were reported in this study. The most common indication for cranioplasty was trauma in twenty two cases 52 % (compound depressed fractures + growing skull fractures + decompressive craniectomy).The most common location was the frontal lobe in fifteen cases 35 %. In 47 %, the split calvarial graft was the most commonly used graft type. The highest percentage of cases showed no complications after follow-up (71 %). Conclusion: Autograft cranioplasty in pediatric population had a 71 % success rate in our series with multiple different options including split calavarial graft, rib graft and repositioning of previously stored craniectomised bone flap. The choice between them depends on age of the patient and size of the defect.